Pengaruh Pencahayaan terhadap Kinerja Karyawan di Kantor Swarna Hutama Loka Asia, Bali - Elena Luwiska Wijanarko; Griffita Liunsanda; Sheryn Meivy Hendra; Yohanes Satyayoga Raniasta (ATRIUM: Jurnal Arsitektur, 2024)
Title: The Lighting Effect on Employee Performance in the Swarna Hutama Loka Asia, Bali Office Lighting is one of the essential aspects to support daily human activities. The result of the reflection of light onto an object allows us to see clearly and comfortably so that the work can be done correctly. A good workspace should fulfill the comfortability aspects of its users. One of them is visual comfort, which affects worker performance and productivity. Optimal employee performance and productivity can be achieved if the comfort points in the workspace comply with standards, i.e., the lighting design provisions for the workspace layout and the required light intensity. The research method used in this study is a comparative method with a combined methods approach, namely by comparing the results of qualitative (respondents' questionnaire) and quantitative (measurement of light intensity and Window Wall Ratio) methods according to SNI 03-6575-2001 standards: Procedures for designing artificial lighting systems in buildings. This method is used to analyze the lighting and visual comfort of the room and its relation to the productivity of Swarna Hutama Loka (SHL) Asia’s office users. Generally, if employees feel comfortable with the workplace's lighting intensity, their performance and productivity will also increase. However, it does not always work in some conditions due to factors other than lighting, such as furniture arrangement and environmental adaptation, which are not included in this research.